2022
DOI: 10.22146/majkedgiind.63382
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adding zirconium dioxide nanoparticle to acrylic denture base on porosity and candida albicans adhesion

Abstract: Acrylic resin is the most common fabricated material for denture bases. ZrO2 nanoparticles can be used as filler to strengthen the physical properties and inhibit the adhesion of acrylic resins. This study aimed to examine the growth of Candida albicans and porosity in reinforced acrylic resin with Zirconium Dioxide (ZrO2) nanoparticles at 2.5% and 5% a concentration targeted for denture bases application. A laboratory experiment study included twenty-seven disc-shaped samples which were divided into three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Their mechanism involves the production of active oxygen species, which inhibit the normal budding process of pore formation in the cell wall. This causes the cell wall to disintegrate via ion outflow, which inhibits fungal growth by disturbing cell function [ 21 , 22 , 23 ]. A denture in the oral cavity is constantly subjected to thermal stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their mechanism involves the production of active oxygen species, which inhibit the normal budding process of pore formation in the cell wall. This causes the cell wall to disintegrate via ion outflow, which inhibits fungal growth by disturbing cell function [ 21 , 22 , 23 ]. A denture in the oral cavity is constantly subjected to thermal stresses.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Antony et al indicated that using ZrO 2 NPs at concentrations of 2.5% and 5% reduced the porosity of the denture base surface and reduced the number of adherent C. albicans . Nevertheless, the same study concluded that 2.5% and 5% ZrO 2 NPs had a fungistatic effect [ 22 ]. Jangra et al found that ZrO 2 NPs mainly targeted Escherichia coli and Staphylococcus aureus bacterial strains and Aspergillus niger fungal strains.…”
Section: Introductionmentioning
confidence: 99%
“…filler is used in research because it produces good dispersion and eliminates aggregation so that the metrics and fillers are more compatible [17]. Anthony, et al (2021) found that the best results were obtained at a concentration of 5% ZrO2 where the porosity at a concentration of 5% was smaller compared to a concentration of 2.5%, so it was concluded that the addition of more filler could reduce the porosity of the composite [18] this affects the strength of the denture teeth composite.…”
Section: Preparation Of Denture Teeth Compositementioning
confidence: 99%